Penggunaan Finite State Machine Untuk Navigasi dan Kendali Ar.Drone Quadcopter Menggunakan Microsoft Kinect - Reza Tanjung Ahmad Fauzi; Gembong Edhi Setyawan; Wijaya Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In the life of the general public and professional, the need for computer-based systems that robots have increased rapidly. Along with the increasing needs of the community on the use of robots in everyday life, the capabilities of the robots are also increasing with the aim that robots can complete the tasks assigned by human. One important aspect when a robot collaborates with a human is the security of the robot when performing tasks in the human environment both to the general public and professional. One of the steps applied to the robot in order to increase the security level of the robots when operating within the human environment is to apply finite state machine method into the robot system. Finite state machine is an abstract machine consisting of a set of conditions, an initial condition, an input, and a transition function that maps the input and the current state to the next condition. In this research, the implementation of finite state machine method in quadcopter control and navigation system using the Kinect sensor. Then compare the quadcopter control and navigation system with the Kinect sensor that applies finite state machine method with quadcopter control and navigation system with Kinect sensor which does not apply finite state machine method. Based on the combination of motion testing that was carried out fourteen times using the finite state machine method on this system, the results of quadcopter movement were found which did not occur in collisions of objects around the quadcopter.